2005
DOI: 10.1007/s11274-005-9011-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low pressure-homogenized lactic cultures on the development of proteolysis in cheese slurry

Abstract: The aim of this study was to determine the effect of low pressure-homogenization of lactic acid bacteria (LAB) on the development of proteolysis in the slurry medium. For the slurry, the milk was pasteurized at 65°C for 30 min, cooled to 32°C and coagulated. The curd obtained was blended; the dry matter was adjusted to 30% by adding distilled water, placed into the flasks and autoclaved. The LAB Lactococcus lactis subsp. lactis, Lactococcus lactis subsp. cremoris, Lactobacillus delbrueckii subsp. bulgaricus, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Improved sensory properties have also been obtained through modulation of some physico-chemical and technological processes (Gardini et al 1999; Patrignani et al 2006, 2007). HPH treatment has potential for several applications such as cell disruption for the recovery of intracellular bio-products and enzymes (Kelly & Muske, 2004), control and enhancement of proteolytic and fermentative activities of some Lactobacillus species (Coskun, 2006; Lanciotti et al 2007), modification of the microstructure and rheology of food emulsions (Guerzoni et al 1997; Floury et al 2000), increasing cheese yield (Lanciotti et al 2004a; Sandra & Dalgleish, 2005; Burns et al 2008). HPH also has great potential for the development of new products, differentiated from traditional products by sensory and structural characteristics or functional properties (Guerzoni et al 1999; Lanciotti et al 2004b; Madadlou et al 2006).…”
mentioning
confidence: 99%
“…Improved sensory properties have also been obtained through modulation of some physico-chemical and technological processes (Gardini et al 1999; Patrignani et al 2006, 2007). HPH treatment has potential for several applications such as cell disruption for the recovery of intracellular bio-products and enzymes (Kelly & Muske, 2004), control and enhancement of proteolytic and fermentative activities of some Lactobacillus species (Coskun, 2006; Lanciotti et al 2007), modification of the microstructure and rheology of food emulsions (Guerzoni et al 1997; Floury et al 2000), increasing cheese yield (Lanciotti et al 2004a; Sandra & Dalgleish, 2005; Burns et al 2008). HPH also has great potential for the development of new products, differentiated from traditional products by sensory and structural characteristics or functional properties (Guerzoni et al 1999; Lanciotti et al 2004b; Madadlou et al 2006).…”
mentioning
confidence: 99%
“…These findings indicate that increase in homogenization pressure from 0 to 13.80 MPa resulted in increased acid tolerance of the yogurt cultures (LB-12 and ST-M5). Coskun (2006) found that homogenization of lactic acid Shah and Jelen (1990) reported that at pH 1.5, L. delbrueckii ssp. bulgaricus and L. acidophilus proved to be more acid resistant than S. thermophilus strains.…”
Section: Acid Tolerancementioning
confidence: 99%
“…Homogenization pressures of 6.90 and 10.34 MPa improved the protease activity of S. thermophilus significantly (P < 0.05; Table 3), as determined by the Pr > t values of the differences of the least squares means. Coskun (2006) also stated that addition of attenuated (homogenized) cultures subjected to the homogenization pressure of 30 MPa enhanced the proteolytic activity of the lactic acid bacteria (L. lactis, L. cremoris, L. delbrueckii ssp. bulgaricus, and S. thermophilus).…”
Section: Protease Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cheese slurry system that allows cheese to ripen at 30°C for 5 to 30 days has been used as a quick tool to evaluate the contribution of different components into the cheese (Kristoffersen et al 1967;Farkye et al 1995;Muehlenkamp-Ulate and Warthesen 1999;Coskun 2006;Kumar et al 2007).…”
Section: Introductionmentioning
confidence: 99%